THE LATEST TRENDS IN DEVELOPMENT OF DISTANCE EDUCATION IN UKRAINE - V. Kosyk (Kherson State University, 2013)
This article analyzes the current state of distance education in Ukraine and highlights the urgent problems to solve which а new Statute on distance learning has been worked out.